Barriers to Justice in Sierra Leone - Dale, Pamela (World Bank, Washington, DC, 2018)
Sierra Leoneans attempting to access justice through the country's complex legal system are presented with a number of barriers. These obstacles can be broadly broken down into those that are the results of the system's costs (including costs of services, fines, time, and transportation) or structure (court infrastructure, skills of officials, and lack of ownership), or, in the case of the formal justice system, its incompatibility with social norms. One of the foremost barriers preventing access to Sierra Leone's justice systems, both formal and informal, is cost. With a Gross Domestic Product (GDP) per head of $548 in 2005, Sierra Leone is one of the world's poorest nations. This extreme poverty magnifies the effects of conflicts that are small by western standards, and also amplifies the costs of recovery. The costs of accessing justice in Sierra Leone come in a variety of forms, including direct costs of services, fines, time, and transportation. In Sierra Leone's formal courts, where an inadequate legal aid structure makes contesting parties responsible for court fees, legal representation, and other service fees, costs are prohibitively high for all but the wealthiest of citizens. Yet even in local courts, which are designed to be closer to the people, interviews suggest that costs are often too high to encourage use. The World Bank's justice for the poor program will continue to engage with justice reform efforts led by local and international civil society, international organizations, and formal and informal institutions in an effort to improve and enhance access to justice for the poor.